2005
DOI: 10.1111/j.1532-7795.2005.00091.x
|View full text |Cite
|
Sign up to set email alerts
|

A Latent Growth Curve Analysis of the Structure of Aggression, Drug Use, and Delinquent Behaviors and Their Interrelations Over Time in Urban and Rural Adolescents

Abstract: Latent growth curve analysis was used to examine the structure and interrelations among aggression, drug use, and delinquent behavior during early adolescence. Five waves of data were collected from 667 students at three urban middle schools serving a predominantly African American population, and from a more ethnically diverse sample of 950 students at four rural middle schools. One set of models focused on changes in individual behaviors; the other on changes in a global problem behavior factor. Models with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
103
3
5

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(126 citation statements)
references
References 57 publications
15
103
3
5
Order By: Relevance
“…Regarding the use of other psychotropic substances and narcotics, cigarettes and marijuana were substances that most participants reported consuming. In this direction, considering consumption patterns of legal and illegal drugs specifically among adolescents in conflict with the law, studies show that early drug use predisposes adolescents to engage in violation practices early, suggesting that the use of illicit substances makes them vulnerable to adopting criminal behaviour 11,20,21 . In addition, there is evidence on the consequences of the use of substances at this stage of development, as noted by Rigoni and coworkers for example, where they found that adolescents who use marijuana may have their neurological functioning affected by drug use, since they have a worst cognitive performance when compared to adolescents who do not use marijuana 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the use of other psychotropic substances and narcotics, cigarettes and marijuana were substances that most participants reported consuming. In this direction, considering consumption patterns of legal and illegal drugs specifically among adolescents in conflict with the law, studies show that early drug use predisposes adolescents to engage in violation practices early, suggesting that the use of illicit substances makes them vulnerable to adopting criminal behaviour 11,20,21 . In addition, there is evidence on the consequences of the use of substances at this stage of development, as noted by Rigoni and coworkers for example, where they found that adolescents who use marijuana may have their neurological functioning affected by drug use, since they have a worst cognitive performance when compared to adolescents who do not use marijuana 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Esse fato confirma que, quando o uso de drogas ocorre precocemente, existe uma chance maior de o adolescente se envolver mais cedo com as infrações, sugerindo que o uso de drogas o deixa mais vulnerável aos comportamentos de risco, como a prática de infrações 21,29,30,31 .…”
Section: Discussionunclassified
“…Segundo estudos longitudinais realizados na França e na Suíça 21 , as infrações geralmente precedem o consumo de substâncias psicoativas, e quanto mais os adolescentes cometem delitos, tanto mais usam drogas.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Some of the factors that have been related to the use of substances at this stage include certain personality traits, with deviant social behaviour standing out (Farrell, Sullivan, Esposito, Meyer and Valois, 2005;Graña, 2000;Jessor and Jessor, 1980). Moreover, family factors such as the way parents bring up their children (Beck, Boyle and Boekeloo, 2004;Becoña, 2002;Cava, Murgui and Musitu, 2008;De la Villa, Rodríguez and Sirvent, 2006;Espada and Méndez, 2002;Fernández, Secades, Vallejo and Errasti, 2003;Gerra, Angioni, Zaimovic, Moi, Bussandri, Bertacca et al, 2004;Martínez and Robles, 2001;Mewse, Eiser, Slater and Lea, 2004;Muñoz and Graña, 2001;Olsson, Coffey, Toumbourou, Bond, Thomas and Patton, 2003) or a "distant" relationship between parents and their children (Brook, Brook, De La Rosa, Whiteman, Jonson and Montoya, 2001) have also been shown to be related to substance use at this stage of development.…”
mentioning
confidence: 99%